Barriers to network-specific innovation - Antoine Martin; Michael J. Orlando (Federal Reserve Bank of New York, 2005)
We examine incentives for network-specific investment and the implications for network governance. We model an environment in which participants that make payments over a network can invest in a technology that reduces the marginal cost of using the network. A network effect results in multiple equilibria; either all agents invest and network usage is high or no agents invest and network usage is low. When commitment is feasible, the high-use equilibrium can be implemented; however, when commitment is infeasible, fixed costs associated with use of the network-specific technology result in a holdup problem that implements the low-investment equilibrium. Thus, governance structures necessary to achieve commitment will be preferred to those necessary merely to achieve coordination. For example, mutual ownership by network users may emerge where users face risk of ex post renegotiation. Such a governance structure will also be sufficient to avoid the network effect.
Keywords: L14; E59; F29; 330; holdup; network; commitment; payments; Netzeffekt; Monopol; Investition; Theorie